CoAl2O4/Kaoline Hybrid Pigment Prepared via Solid-Phase Method for Anticorrosion Application - Zhang, Anjie; Mu, Bin; Wang, Xiaowen; Wang, Aiqin (Frontiers in Chemistry, 2018)
In this study, kaoline is incorporated to prepare CoAl2O4 /kaoline hybrid pigments via traditional solid-state reaction, and the introduction of kaoline decreases the preparation temperature for formation of spinel CoAl2O4, and reduces the production cost of cobalt blue as well. More importantly, kaoline may participate in the crystallization of spinel CoAl2O4 during calcining process, and the hybrid pigments prepared using 8.1% Co3O4 and 81.5% kaoline features bright blue and good chemical resistance. Due to the synergistic effect between the sheet-like kaoline and the loaded CoAl2O4, the as-prepared CoAl2O4/kaoline hybrid pigments can be incorporated into epoxy paint system to obtain the high-performance blue anticorrosion coating, especially for acetic acid-salt fog corrosion.